University Students’ Attitude, Self-Efficacy And Motivation Regarding Leisure Time Physical Participation - Lim , Khong Chiu (Penerbit Universiti Sains Malaysia, 2009)
The purpose of this study is to identify the influences of attitude, self-efficacy, and motivation on leisure time physical activity participation in students at local public universities. The theories of planned behaviour and self-efficacy were used as a theoretical framework. The study sample is comprised of 551 males and 801 females who were selected by means of random cluster sampling. Questionnaires were utilised to collect data. The results of the study showed that there were positive correlations between leisure attitude, motivation, and self-efficacy and leisure time physical activity participation among undergraduate students. The results also revealed that motivation and self-efficacy were the best predictors of leisure time physical activity participation. This study suggests that, in the effort to encourage the student’s leisure time physical activity participation and involvement, university management should plan and organise programmes to develop positive attitudes among students, increasing their self-efficacy and motivation level for physical activity participation.